Development of the embolization technique for cerebral and spinal marrow arteriovenous malformations, and its clinical basis. - Goulão, A (1990)
The authors revised 4 cases of large AVM's--3 cerebral and 1 medullary--illustrating the evolution of their technique of endovascular occlusion. These embolizations always preceding the surgery have their interest discussed in terms of the clinical grounds, the easiest access to the nidus and the possibilities of preventing some of the surgical risks.